Note: comparison of colour techniques to measure chocolate fat bloom - Kumara, B.; Jinap, S.; Che Man, Y.B.; Yusoff, M.S.A. (SAGE Publications, 2003)
A combination of digital camera, computer and graphic software can provide a less expensive and more versatile technique to determine the changes of colour on chocolate's surface in fat bloom assessment compared to instrumental colour measurement. Both techniques were applied and compared to measure the colour profiles at various locations on the surface of bloomed chocolates. Pearson correlation coefficients and sample paired t-test on whiteness index (WI) and L*a*b* values were calculated. The value of WI of chocolate samples from instrumental technique was in the range of 35.8-44.3 with a coefficient of variance (CV) ranging from 0.0 to 0.9%. Meanwhile, digital image technique gave a WI value ranging from 35.1 to 45.1 with a CV from 0.1 to 14.2%, respectively. A highly significant correlation was found for the means of WI (R2 = 0.821) and L* (R2 = 0.788) values between instrumental and digital image technique. b* value of digital image also had significant correlation with the instrumental data (R2 = 0.756). However, there were significantly different measurements in the values obtained (p<0.001) by both techniques. Thus, b* as well as a* values could not be used as a colour indicator in this study. The results suggested that though the digital image provided good measurement of WI and L*, the colour measurements of digital image were less precise as compared to the instrumental technique, therefore results from the digital image should be interpreted with caution.